EFFECT OF FOLIAR FERTILIZATION WITH LIQUID NITROGEN AND BENZYL AMINO PURINE ON SENESCENCE, NITROGEN MOBILIZATION AND CARBON CONTENT IN COWPEA VARIETIES - Mohammad, M. (FUDMA Journal of Sciences, 2023)
The effects of liquid nitrogen fertilizer (150% N) and Benzyl Amino Purine (200ppm BAP) were investigated on senescence, nitrogen mobilization and carbon content in two cowpea varieties during the rainy and dry seasons. This study was conducted in the screen house at the University of Lagos located in the south western part of Nigeria. There were four treatments (nitrogen fertilizer, BAP, combined treatment of liquid nitrogen fertilizer and BAP and then the control). Data was collected on senescence, nitrogen and carbon content. The result on senescence showed that onset of senescence, days to 50% senescence, 90% senescence and days to total death of the plants occurred earlier in IT89KD – 288 than in Kanannado, while comparison between the treatments showed that senescence started earlier in plant treated with single treatment of liquid nitrogen fertilizer (15%N). Between the two seasons, senescence started earlier in the dry season than in the rainy season. Result on Nitrogen showed that between the two varieties, IT89KD – 288 had greater Nitrogen content than Kanannado at 6 and 9 weeks, but at week 12 there was a decrease of the nitrogen in the leaves of IT89KD-288 then in Kanannado. The treatment with the highest Nitrogen content in the varieties was combined treatment of 150% N fertilizer + 200ppm BAP at 6, 9 and 12 weeks, followed by Nitrogen fertilizer (150% N) at 6 weeks only, but at 9 and 12 weeks when subsequent analysis was carried out there was